Analisis Self-Efficacy Mahasiswa Universitas Nurtanio pada Mata Kuliah Kalkulus Integral - Simangunsong, Herlina; Agustianti, Rifka (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze student self-efficacy where the research subjects are third semester students of Nurtanio University Bandung in the Integral Calculus course. This study uses a descriptive quantitative method where the sample is taken using a purposive sampling technique. The results of the study show that in general the majority of students in the Integral Calculus course have self-efficacy in the medium category, which is 53.33% of the total number of students with the conclusion that most of the self-efficacy in the magnitude and generality dimensions shows a medium category of 70% and 56.67% of the total number of students, while most of the students' self-efficacy in the strength dimension shows a high category of 40% of the total number of students. Keywords : Self-Efficacy; Integral Calculus; Student